Aktualisasi Manajemen Peningkatan Mutu Berbasis Madrasah - Hamid, Abdul (At- Ta'lim : Jurnal Pendidikan, 2018)
Along with the changing times towards progress, in the era of increasingly free competition like today, educational institutions are required to be able to provide quality education that bemutu because educational institutions that lack of quality over time will be abandoned by society and eliminated by itself. The form of efforts to improve the quality of education undertaken by the government is to establish a policy of quality management based on madrasah by delegating authority from the center to the madrasah (madrasah), where the madrassas are given the flexibility and authority to organize and implement up to evaluate the education carried outTitle of actualization of quality improvement management based on madrasah. While the formulation of the problem is how the actualization of quality improvement management based on madrasah, what are the supporting and inhibiting factors in actualizing the management of quality improvement based on madrasah.The result of the research shows that the actualization of management of quality improvement of education can be implemented well, because madrasah is basically the existence of madrasah from, by and for society and it is time for madrasah based quality management is applied in madrasah to improve education quality Actualization of madrasah based quality improvement management as a national policy, firstly do program planning and situation analysis to know the target to be achieved and do SWOT analyst to know how far the readiness of madrasah in order to improve the quality of educationAfter MPMBM planning is completed by giving birth to the program that must be implemented, the head of the madrasah performs the division of workload by providing a proportional portion to each individual or group. In evaluating the head of the madrasah perform regular evaluations every week and any problems Keywords: Quality Improvement Management, Madrasah Based Quality of Education